Analisis studi kelayakan usaha peternakan ayam petelur mitra satwa ps - Ratnasari, Aprilia Dwi; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
This article discusses a business feasibility study on one of the laying hen farming businesses in the Blitar Regency area, namely Mitra Satwa PS. This business feasibility study is carried out to see whether a business plan that has been prepared is feasible or not and if it has been carried out regularly whether the maximum level of profit can be achieved or not within the specified time period. This business feasibility study assessment was carried out by assessing 5 aspects, namely legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, as well as management and human resources aspects. Based on the results of the business feasibility study analysis on the Mitra Satwa PS laying hen farm, it was concluded that this business is feasible to continue with several notes that need to be improved in the future so that this business is more advanced and develops in the future. future. For example, in terms of legality, businesses need to renew their business permits, take advantage of current technological developments to simplify business and make operations more effective, carry out AMDAL analysis and divide job desk work and appoint people in charge of each division to make the control process easier.